Effects of temperature and a piscivorous fish on diel winter behaviour of juvenile brown trout (Salmo trutta). (24th July 2019) - Filipsson, Karl; Bergman, Eva; Österling, Martin; Erlandsson, Ann; Greenberg, Larry; Watz, Johan
Abstract: Low winter temperatures constrain predator‐detection and escape capabilities, making poikilotherms vulnerable to predation. Investigations of temperature effects on predator–prey interactions can therefore be of special importance in light of ongoing climate change, where winter temperatures are predicted to increase substantially at northern latitudes. Behavioral responses of stream fishes to terrestrial predators in winter are well recognised, whereas responses to predatory fish have received little attention. Using stream flumes, we examined the anti‐predator behaviour of one‐summer‐old brown trout ( Salmo trutta ) at 3 and 8°C in the presence and absence of burbot ( Lota lota ) under night, dawn, and daylight conditions. Burbot was placed upstream of the trout, separated by net screens. Lower temperature and the presence of burbot reduced trout activity. Light increased trout shelter use, and trout sheltered more in the presence of burbot. An interaction between the presence of burbot and light conditions affected trout position in the flumes: at night and dawn, trout positioned themselves further downstream when burbot were present than when absent, whereas during the day, trout maintained the same position in the presence or absence of the predator. Our results suggest that piscivorous fish, in addition to terrestrial predators, shape the behaviour of prey fishes in streams during winter. We show how predator avoidance results in altered diel patterns of juvenile brown trout under winter conditions, and that temperature has additional effects on trout behaviour.